Radiological Hazards of Natural Radionuclides in Building Materials in Katsina State, Nigeria: A Systematic Review - Gambo, Nura; Dahuwa, Dahiru (FUDMA Journal of Sciences, 2026)
Trace amounts of radioactive elements are naturally present in building materials and may contribute to human exposure to ionizing radiation. This systematic review evaluates the concentrations of naturally occurring radionuclides including 226Ra, 232Th, 40K commonly used construction materials in Katsina State, Nigeria, and comparable geological environments. This systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. A total of 345 records were initially identified from major scientific databases and institutional reports published between 2010 and 2025. After screening and eligibility assessment, 30 relevant studies were included for qualitative synthesis, while 20 studies containing detailed radiological parameters were selected for comparative analysis. Only peer-reviewed studies reporting activity concentrations of radionuclides and radiological hazard indices in building materials, particularly within Nigeria and similar geolo gical environments, were included in the review. Reported activity concentration values ranged from 4.41–93.00 Bq/kg for 226Ra, 16.71–320.00 Bq/kg for 232Th, and 68.03–673.00 Bq/kg for 40K across reviewed studies. Most evaluated radiological hazard indices, including radium equivalent activity and external hazard index, remained below internationally recommended safety limits. Gamma-ray spectroscopy and X-Ray Diffraction (XRD) were the major analytical methods employed. However, regional variations linked to geological formations, inadequate monitoring facilities, weak regulatory implementation, and limited integration of mineralogical analysis remain significant challenges in Nigeria. The review highlights the importance of continuous radiological monitoring, improved regulatory control, and standardized assessment procedures to ensure the safe and sustainable use of building materials.